Slum Management Analysis Using Bibliometric Analysis - Putra, Muhammad Andhika Sukma; Santosa, Mohammad Rizky Nur; Nurmandi, Achmad; Fridayani, Helen Dian; Atmojo, Muhammad Eko (Jurnal Ilmu Administrasi Negara (JUAN), 2024)
The presence of slum areas has emerged as a critical issue, sparking extensive debates across various sectors. Slum settlements, characterized by substandard living conditions due to factors such as high building density, inadequate infrastructure, poor sanitation, and health risks, pose significant challenges for urban management. This study aims to analyze government policies addressing slum settlements and evaluate building rehabilitation policies to tackle these issues effectively. Utilizing bibliometric analysis and VOSviewer, the research explores trends and developments in slum area management worldwide. The findings highlight that slum formation is often rooted in cultural and socio-economic realities, especially in developing countries, where urbanization and migration lead to overcrowding in cities. Slums reflect a harsh reality for impoverished populations striving for better living conditions. Addressing slums requires multi-sectoral collaboration involving governments, private sectors, and communities, supported by well-defined legal frameworks and sustainable urban planning. Key insights from the bibliometric analysis, based on 196 articles from Scopus, reveal increasing academic interest in slum management from 2013 to 2023, focusing on themes like governance, sustainability, pollution, and urban development. Results from VOSviewer indicate clusters of keywords such as "sustainable development," "population density," and "environmental quality," emphasizing the need for comprehensive strategies. Effective slum management involves equitable access to resources, economic empowerment, and social justice. This research underscores the necessity for innovative policies, such as integrating renewable energy and water-sensitive urban design, to rehabilitate slum areas sustainably.